The estimation of adopted mortality and morbidity rates using model and the phase type law: the Turkish case. Issue 9 (21st October 2019) - Akat, Fulya; Selcuk-Kestel, A. Sevtap; Tank, Fatih
Abstract: This paper aims to estimate mortality rate, morbidity-mortality rates of a chronic disease utilizing phase type law in the frame of two and three state processes. The application on commonly used mortality tables in Turkey are adopted to process to estimate the future mortalities with respect to phase type distribution for the purpose of justifying. Using one absorbing state, two and three state Models calculate the time until absorbing of the death and death by phase type distribution for each gender. Consequently, the 3-state probabilities in estimating the mortality-morbidity rates of IHD for Turkish population yield a significant information on the health management and pricing health insurance products.